Characterization of heavy metals in soils from typical tobacco cultivated areas, China. Issue 2 (31st October 2016) - Lin, Beisen; Gao, Huajun; Lai, Hongmin; Li, Chunhua; Wang, Quan
Abstract : The heavy metal in tobacco has been widely concerned for the toxicity and bioaccumulation. Heavy metal in tobacco is of extremely related with the corresponding concentration in soil. One hundred soil samples were collected from five typical tobacco cultivated areas to evaluate the environmental quality and health implications. The inductively coupled plasma mass spectrometry was employed to determine the concentrations of heavy metals (As, Cd, Cr, Cu, Hg, and Pb). The geo‐accumulation index and potential health risk assessment were performed to investigate the environmental quality and health risk. The concentrations of As, Cd, Cr, Cu, Hg, and Pb are ranged from 0.40 to 112 mg/kg, 0.07 to 4.22 mg/kg, 5.52 to 338 mg/kg, 3.40 to 64.5 mg/kg, 0 to 1.62 mg/kg, respectively. The concentrations of heavy metals are various among the five different typical cultivation areas. The elevated concentrations of heavy metals in the selected soils suggesting that these heavy metals may be derived from anthropogenic sources i.e. industrial and agricultural activities. The results shown that the soils in the Jingxi, Longlin, and Debao County are posed to a moderately to heavily contamination for Hg and Cd. The noncarcinogenic and carcinogenic effects (except Lingyun County) caused by heavy metal exposure is regarded as acceptable. The Lingyun County soil should be paid more attention due to the unacceptable level of carcinogenic risk. As, Cd, Hg, and Cr are regarded as the priority control metals. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 483–488, 2017